Evaluation of Indian bean genotypes under hot arid environment (Indian Journal of Arid Horticulture, 2025)
Horticultural and morphological studies among twelve genotypes of Indian bean were made for growth, pod quality and yield contributing characters under arid environment to select desirable types for commercial exploitation. Significant variation in all the important characters was observed in the genotypes especially for days to first picking, pods per plant, pod yield per plant, fresh weight, length and width of pod and these characters are of great significance in redesigning the plant architecture of the genotype having higher early yield with better quality pods. The genotypes AHDB- 16 (818.0 g). AHDB-15 (707.1 g), AHDB-3 (698.3 g) and AHDB-7 (147.7 g) were found to be promising on the basis of important traits like plant type, fruiting, quality of pod and yield under arid conditions.
Keywords: Indian bean; Lablab purpureus; arid environment